2009
DOI: 10.1016/s0034-7094(09)70085-6
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia in a Patient With Congenital Insensitivity to Pain and Anhidrosis

Abstract: Although there is insensitivity to pain, some patients present tactile hyperesthesia that can cause unpleasant feelings during surgical manipulation. Despite reports in the literature of patients undergoing neuroaxis blocks, and even procedures without anesthesia, intravenous anesthesia, which provided adequate conditions for the anesthetic-surgical procedure was used in this case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
8
0
2
Order By: Relevance
“…Due to the insensitivity to pain in these patients, several issues are made difficult for anesthetists in surgical procedures, such as whether or not to administer anesthesia, and if so, the choice of anesthesia type and drugs, providing sufficient depth of anesthesia, the necessity of monitoring body temperature because of impaired ther- can occur in the hemodynamic parameters 10,11 . Therefore, there is an absolute need for the administration of anesthesia during a surgical procedure and it has been reported that the type of anesthesia should be general anesthesia as the majority of these cases are mentally retarded pediatric cases 10,12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the insensitivity to pain in these patients, several issues are made difficult for anesthetists in surgical procedures, such as whether or not to administer anesthesia, and if so, the choice of anesthesia type and drugs, providing sufficient depth of anesthesia, the necessity of monitoring body temperature because of impaired ther- can occur in the hemodynamic parameters 10,11 . Therefore, there is an absolute need for the administration of anesthesia during a surgical procedure and it has been reported that the type of anesthesia should be general anesthesia as the majority of these cases are mentally retarded pediatric cases 10,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is an absolute need for the administration of anesthesia during a surgical procedure and it has been reported that the type of anesthesia should be general anesthesia as the majority of these cases are mentally retarded pediatric cases 10,12 . In the case reported here, it was thought that ketamine and inhalation anesthesia would be sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…About the anesthetic considerations [ 39 , 40 ], although pain stimuli are absent, anxiety associated with surgical procedures may generate stress and consequent hemodynamic instability. It is necessary to minimize preoperative apprehension and anxiety with the use of sedatives.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Despite patients are insensitive to pain, general anesthesia or sedation may be necessary because of disturbing conditions such as tactile hyperesthesia during the surgical procedure. [9] Experience on anesthesia management of these patients is limited due to few number of cases. We aimed to present our experience about the anesthesia management of two siblings with CIPA syndrome.…”
Section: Introductionmentioning
confidence: 99%